UTAUT Model Integration Analysis in the Context of BCA e-Banking Adoption - Shella; Juven Gautama; Joyce Chrissy; Jenny Oei; Hendiko (LPPM Universitas Respati Indonesia, 2024)
This study aims to analyze the UTAUT Model Integration in the context of e-Banking BCA adoption. Research related to the use of Internet Banking often uses E-Service Quality. Therefore, it is necessary to do research about the effect of service quality using BCA Internet Banking. The Study was conducted by determining a sample of 121 student who use BCA Internet Banking. The research used Structural Equation Modeling (SEM) analysis with IBM SPSS AMOS V.20. The finding show that: (1) Web design perceptions will not have a positive relationship with the intention of adoption users and will have a positive relationship with the intention of adoption users; (2) Service perceptions to consumers will not have a positive relationship with the of adoption users and will be positively related to the intention of adoption users; (3) Perception of assurance will not be positively related to the intention of adoption users and will be positively related to the intention of adoption users; (4) Perception of reliability will not be positively related to the intention of adoption users and will be positively related to the intention of adoption users. From the research results, it can be seen that Assurance and Reliability have a significant effect on User Intention to adopt Internet Banking, however Web Design and Customer Service do not have a significant effect on User Intention to adopt Internet Bankin Keywords: UTAUT, E-Service Quality, SEM, User Intention to adopt Internet Banking.